Mass media information can facilitate early diagnose of hereditary angioedema: Case series study - Isao Ohsawa; Daisuke Honda; Yuya Nakamura; Hiromichi Gotoh; Yoshikazu Goto; Yusuke Suzuki; Yasuhiko Tomino (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2018)
Background: A patient's motivation for consulting a physician is paramount to the first steps of achieving an early diagnosis of hereditary angioedema (HAE). Understanding what triggers this motivation can help in the design of strategies to increase the number of visits to a specialist physician following early symptoms of HAE. The aim of the present study was to identify the reasons that led patients to seek the opinion of an HAE expert physician. Methods: The number of patients who had visited a specialist outpatient clinic for HAE was determined. All patients were asked what motivated them to seek medical consultation. Clinical data and blood samples were collected to establish a diagnosis.  Results: Seventy patients visited the clinic within a 30-month period between August 2015 and January 2018. Seven of these patients were diagnosed with HAE. The main source of evidence that prompted the visit to the specialist clinic was websites (67.1%), followed by newspapers (15.7%) and information provided by the home doctor (14.2%). The number of patients per month increased after a rise in the number of publications about HAE in newspapers and websites. Conclusion: Mass media publications are an efficient way to motivate patients to visit an HAE expert physician.